Derogatoria del art. 97.1 del Código del Trabajo que limita las utilidades al trabajador - Bustamante Jaramillo, Alvaro Francisco (2015)
The Article 97.1 of the Labour Code clearly states: "Participation of workers in utilities company.- The employer or enterprise recognizes the benefit of their employees to fifteen percent (15%) of the net profits. This percentage is distributed as follows: Ten percent (10%) will be divided for company employees, without regard to the remuneration received by each of them during the year for the cast and will be delivered directly to the worker. Five percent (5%) remaining will be delivered directly to employees of the company, in proportion to their dependents, meaning they the spouse or common-law, children under eighteen and disabled children of any age. The distribution will be done through the majority association of employees of the company and in proportion to the number of these dependents, duly accredited by the worker to the employer. If there is no association, it will direct delivery. There Were those not worked the full year, they will receive such shares proportional to the length of service ... " But of that statute, the Labour Code by recent reform, limits participation on profits by the worker and stipulates a limit, note: "Art. 97.1.- limit the distribution of 'profit sharing profits distributed to the workers as it stated in the previous article may not exceed twenty Unified Basic salaries of workers in general. If the value of these exceed the prescribed amount, the balance shall be paid to the regime of solidarity Social Security benefits. The competent labor administrative authority will issue the necessary ministerial agreements for the proper application of what is stated in this article". That is, in companies whose earnings are above twenty basic unified salaries, which means more than $ 8496, the worker may not perceive and balance shall be paid to the system of benefits the Ecuadorian Institute of Social Security. This limits the rights of workers, it is not desirable that the rights of workers, who have the inalienable category is limited. Given this problem, by running my research I prove to be repealed Art. 97.1 of the Labour Code for violating the constitutional, economic and labor rights of people